SOME MORE NOTES ON THE BOND YIELD PROBLEM: SERIAL BONDS. - Snyder, Ralph W. (The Accounting Review, 1953)
Abstract In the July 1952, issue of the "Accounting Review,"under the title "Some Notes on the Bond Yield Problem," the author discussed the application of a modified or improved Newton's correction formula to the problem of finding the accurate yield on a bond, the improved formula having been briefly set forth in an earlier paper by Hugh E. Stelson,' who had drawn it from one of the mathematical journals. This article includes the continuation of numbers of formulas and equations herein from where they stopped in the preceding article. With serial bonds, the problem of finding the initial approximation to the yield rate is more acute than it is with a single bond. This article also discusses the matter appearing in the thirteen pages of Mr. FitzGerald's article in the "Accounting Review," for January, 1953, on accounting for variations in gross profit.